2017
DOI: 10.4172/2572-5130.1000144
|View full text |Cite
|
Sign up to set email alerts
|

Posterior Reversible Encephalopathy Syndrome (PRES) Secondary to Severe Pneumonia

Abstract: Posterior reversible encephalopathy is a rare neurological disease. The association between Posterior reversible encephalopathy syndrome and severe pneumonia is not well described in the available medical literature. We describe a case of a 51 year old female presented to our hospital with sudden loss of vision in both eyes in the background history of pneumonia who recovered completely with treatment. This case report elaborates the very rare entity of posterior reversible encephalopathy syndrome secondary to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“… 27 Infectious diseases such as meningitis, acute gastro-enteritis (AGE), malaria, pneumonia, sepsis, and septic shock have been identified as the commonest causes of admission into emergency wards in Nigeria, 22 , 23 have also been implicated in the etiology of PRES. 46 - 51 These have sometimes also been misdiagnosed as PRES. 41 - 43 Other authors have also identified epileptic seizures, encephalopathy, visual deficits, hypertension, chemotherapy, and renal failure as best predictors of PRES in children.…”
Section: Current Status Of Knowledgementioning
confidence: 99%
“… 27 Infectious diseases such as meningitis, acute gastro-enteritis (AGE), malaria, pneumonia, sepsis, and septic shock have been identified as the commonest causes of admission into emergency wards in Nigeria, 22 , 23 have also been implicated in the etiology of PRES. 46 - 51 These have sometimes also been misdiagnosed as PRES. 41 - 43 Other authors have also identified epileptic seizures, encephalopathy, visual deficits, hypertension, chemotherapy, and renal failure as best predictors of PRES in children.…”
Section: Current Status Of Knowledgementioning
confidence: 99%